Guarantee loans for urban agriculture in Gampaha, Sri Lanka - Amerasinghe, Priyanie H.; Hettige, V.; Wijenayake, K. (2013)
Agricultural development towards security of food, nutrition and livelihood is high on the political agenda in Sri Lanka. Recently, national priorities have included the development of food-secure and resilient cities; in this regard, the Western Province has been a forerunner, having commenced its urban agriculture campaign as early as 2000.